Landau theory-based relaxational modeling of first-order magnetic transition dynamics in magnetocaloric materials. (13th March 2023) - Costa, Rui M; Lovell, Edmund; Almeida, R; Pinto, R M C; Cohen, Lesley F; Pereira, A M; Araújo, João P; Belo, J H
Abstract: The magnetocaloric effect is often largest within the neighborhood of a first-order phase transition. This effect can be utilized in magnetocaloric refrigeration, which completely eliminates the need for the greenhouse gases utilized in conventional refrigeration. However, such transitions present unique dynamical effects and are accompanied by hysteresis, which can be detrimental for such refrigeration applications. In this work, a Landau theory-based relaxational model is used to study the magnetic hysteresis and dynamics of the first-order magnetic transition of LaFe13− x Si x . Fitting the experimental magnetization data as a function of applied magnetic field under different field sweep rates with this model provided the Landau parameters ( A, B, and C ) and the kinetic coefficient of the studied material. We demonstrate the tendency of the magnetic hysteresis to increase with the magnetic field sweep rate, underlining the importance of studying and minimizing the magnetic hysteresis in magnetic refrigerants at practical field sweep rates. While evaluating the temperature dependence of the time required for a complete transition to occur, a nonmonotonic behavior and a sharp peak were found for temperatures near the transition temperature. Such peaks occur at the same temperature as the peak of the magnetic entropy change for low fields, whereas for higher fields the two peaks decouple. This information is critical for technological applications (such as refrigerators/heat pumps) as it provides guidelines for the optimization of the magnetic field amplitude in order to reduce the transition timescale and consequently maximize the machine operational frequency and amount of heat that is pumped in/out per second.